The Influence of Service Quality and Store Atmosphere on Customer Loyalty through Customer Satisfaction - Furoida, Fatin; Maftukhah, Ida (Universitas Negeri Semarang, 2018)
This study aims to determine the direct indirect influence of service quality, store atmosphere and customer satisfaction as an intervening variable on customer loyalty. The population of this research is customer of Martabak Platinum Ruby Pekalongan Cafe. The number of sample is 116 respondents with purpose sampling technique through likert scale questionnaire. Data analysis using descriptive percentage and path analysis. The results show that service quality affect customer loyalty, store atmosphere affect customer loyalty and customer satisfaction influence customer loyalty and mediate the influence of service quality and store atmosphere on customer loyalty.